Outcomes of modified trapeziectomy with ligament reconstruction tendon interposition for the treatment of advanced thumb carpometacarpal arthritis: Two-year follow-up. Issue 13 (March 2018) - Wang, Tao; Zhao, Gang; Rui, Yong-Jun; Mi, Jing-Yi
Abstract : Abstract: Numerous arthroplasty techniques had been reported for the treatment of thumb carpometacarpal (CMC) joint osteoarthritis. The purpose of our study is to evaluate long-term clinical and radiographic outcomes of patients who underwent modified trapeziectomy with ligament reconstruction tendon interposition (LRTI). Our retrospective study included 20 consecutive patients with advanced thumb CMC arthritis receiving modified trapeziectomy with LRTI (20 thumbs). For clinical evaluation, we assessed visual analogue scale (VAS), Disabilities of the Arm, Shoulder and Hand (DASH) scores and Kapandji index. Additionally, the grip, pinch power and waist flexion power, radial and volar abduction angle were evaluated, As for radiologic evaluation, we just estimated height of the trapezial space. We took 2-year follow-up. All patients showed decreased VAS from 6.8 preoperatively to 1.4. Mean DASH and Kapandji scores were improved from 52.2 preoperatively to 21.6 and from 6.4 preoperatively to 7.4, respectively. Compared to preoperative range of motion (ROM) for radial abduction and volar abduction, both markedly increased at 2-year follow-up (from 61.2 to 80.1, from 60.6 to 78.3, respectively). Besides, mean power improved from 15.9 preoperatively to 21.7 kg at 2-year follow-up for grip power, from 1.9 preoperatively to 3.5 kg at 2-year follow-up for tip pinch; however, mean waist flexion power showed no significant change from 20.5 preoperatively to 19.7 kg at 2-year follow-up. Notably, there was no significant sinking in height of the trapezial space from 10.0 preoperatively to 9.6 mm at 2-year follow-up. NO case had a complication at final follow-up. Modified trapeziectomy with LRTI treating thumb CMC arthritis in Eaton stage III–IV had a satisfactory efficacy. This new procedure is able to provides enough support for thumb to prevents thumb sinking.